Mercury isotopic characterization in fish from aquitanian lakes: potential application on mercury source tracing - Silva, Tiago José Caetano (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017